Validation of a Feed Protocol in a Mouse Model That Mimics Marasmic Malnutrition - Ferreira-Paes, Taiana; Seixas-Costa, Paula; Almeida-Amaral, Elmo Eduardo (Frontiers in Veterinary Science, 2021)
Host nutritional status directly interferes with immunity and/or susceptibility to infectious diseases. To understand the mechanisms behind this relationship, the use of animal models and feeding protocols is necessary. In the literature, studies reporting marasmic malnutrition in mice are not common. In this context, the objective of this study was to validate a feed methodology that mimics marasmic malnutrition, examining the nutritional, biochemical and hematological status of BALB/c mice. Weaned BALB/c mice were or were not fed a restricted diet (36.26% carbohydrate, 8.79% protein, 4.95% fat and 7.62 kJ/100 g). Some malnourished mice underwent a refed process with a control diet (65.93% carbohydrate, 24.18% protein, 9.89% fat and 15.24 kJ/100 g). The nutritional status of the mice was evaluated through phenotypic markers and hematological and biochemical parameters. Our results showed that the restricted diet was able to induce mild malnutrition in mice, resulting in a mouse weight loss of 12%, which could be reversed after refeeding. Malnourished mice demonstrated slow body growth and low body mass index (BMI) values. Malnourished mice also showed physical and behavioral changes, a reduction of 47.5% in leukocyte counts and a 2-fold increase in cholesterol levels. In conclusion, our feeding protocol was able to generate mild malnutrition and cause changes in the nutritional status of mice that could be similar to those observed in marasmic malnutrition.